2010
DOI: 10.11646/zootaxa.2476.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, arrangement and classification of sensilla on the apical segment of labium in Peiratinae (Hemiptera: Heteroptera: Reduviidae)

Abstract: The present paper describes sensory structures on the apical segment of the labium in representatives of the subfamily Peiratinae (Heteroptera: Reduviidae), using the scanning electron microscope. The study is based on dry material representing 19 species and 16 genera. Within Peiratinae thirteen morphologically distinct types of sensilla were identified. Among them were four new types of sensilla (porous placodea sensillum [PPLS], multilobate sensillum [MS], domeelongated sensillum [UDES], and pit peg sensill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 0 publications
6
42
0
Order By: Relevance
“…Consequently, for nepomorphan taxa the five patterns of the distribution of the labial tip sensilla can be presented (above). In comparison with the other heteropteran infraorders it has been observed that the morphology and distribution of the labial tip sensilla in the Nepomorpha are distinctly varied with respect to what has been reported in the Gerromorpha (Brożek and Zettel, in prep), Pentatomomorpha [19, 21], and Cimicomorpha: Reduviidae [15, 25]. In terms of diversity and abundance of the sensory system on the labial tip, the Nepomorpha come second to the Gerromorpha.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Consequently, for nepomorphan taxa the five patterns of the distribution of the labial tip sensilla can be presented (above). In comparison with the other heteropteran infraorders it has been observed that the morphology and distribution of the labial tip sensilla in the Nepomorpha are distinctly varied with respect to what has been reported in the Gerromorpha (Brożek and Zettel, in prep), Pentatomomorpha [19, 21], and Cimicomorpha: Reduviidae [15, 25]. In terms of diversity and abundance of the sensory system on the labial tip, the Nepomorpha come second to the Gerromorpha.…”
Section: Discussionmentioning
confidence: 93%
“…An undifferentiated sensory system occurs in the Pentatomomorpha (e.g., Dysdercus fulvoniger and D. koenigii , D. fasciatus, D. intermedius, Lygus lineolaris, and Neomegalotomus parvus ), where the labium tip usually represents one morphological type of basiconic sensilla functioning as the contact-chemoreceptive sensilla (several pairs), basiconic gustative sensilla (several pairs), and basiconic olfactive sensilla (one or two pairs) [17, 19, 21, 22, 37]. In some of the Reduviidae one type of peg and peg-in-pit sensilla have been noticed [15, 25, 38]. Furthermore, two types of mechanosensilla (small hairs and long bristles) have been identified on the tip of the labium by Bernard [39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations